INCREASING STUDENTS’ CREATIVE ACTIVITY THROUGH INTERACTIVE METHODS IN VISUAL ARTS EDUCATION - Karimova Shamsiyabonu Toxir qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores the role of interactive methods in enhancing students’ creative activity in visual arts education. Emphasis is placed on how interactive teaching strategies, including group discussions, collaborative projects, and hands-on exercises, stimulate students’ imagination, independent thinking, and artistic skills. The study highlights the effectiveness of using both traditional and modern interactive approaches to improve engagement, foster creativity, and develop aesthetic perception. Practical examples of applying interactive methods in classroom settings are provided, demonstrating their impact on students’ overall artistic competence.